Features of the receiving of piezoelectric thin films by plasma spraying of powdery AlN - V. S. Feshchenko; K. N. Zyablyuk; E. A. Senokosov; V. I. Chukita; D. A. Kiselev (Российский технологический журнал, 2020)
Оne of the promising materials in solid state electronics is the AlN compound. A wide range of semiconductor devices are produced from it, such as photodetectors, LEDs, piezoelectric converters, etc. But the widespread use of products based on AlN prevents low manufacturability designs based on it. In this regard, the development of new technologies for the production of devices based on AlN is relevant.The work is devoted to the study of thin AlN films obtained by plasma spraying from AlN powder. The review of existing technologies of production of thin films AlN is carried out.Their advantages and disadvantages are discussed. Information on the modernization of the VUP-5 installation, which allowed to spray the AlN film from the powdered state, is given.One of the significant advantages of the process developed in this work is that the substrate is heated to temperatures no higher than 300 oC, which in turn allows to combine this technology with the technology of silicon semiconductor devices.As a result, films with a thickness of 200 nm on various substrates were obtained and their surface structure was studied. It is shown that AlN films deposited on single crystal substrates such as diamond and silicon have the least roughness, while films on sitall have the worst roughness.The transmission spectra of the obtained AlN films were investigated by IR spectroscopy. With their help, it was shown that a polycrystalline AlN layer oriented in the crystallographic direction 002 is formed on the substrate. The piezoelectric properties of the obtained films were investigated by scanning probe microscopy. It is shown that their piezoelectric coefficient d33 is 60% of the value for a single-domain single-crystal sample for a diamond substrate, which indicates a sufficiently high quality of the resulting film.It is concluded that, although the quality of the layers strongly depends on the substrate, nevertheless, they exhibit a significant piezoelectric effect, which allows the use of this method for the manufacture of piezoelectric sensors, ultrasonic emitters, etc.